Pemberdayaan Remaja Karang Taruna RW 08 Tambun Melalui Pembuatan Macrame Dalam Upaya Minat Berwirausaha - Perdhana , Timorora Sandha; Thamrin, Djuni; Fitriani, Yulia; Khasanah, Fata Nidaul (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
Entrepreneurship is the potential for development, both in terms of quantity and quality of entrepreneurship itself. Aside from being a skill, entrepreneurship is also very important knowledge because through entrepreneurship a person can acquire, channel and develop his creativity to be used as income to be used in everyday life. Solutions to problems experienced by partners in this community service activity include a lack of knowledge about the interest in entrepreneurship to support the improvement of youth skills. From the lack of knowledge related to entrepreneurship, it can result in problems experienced 1) limited skills so there is no income to develop youth organizations 2) fostering interest in entrepreneurship as a form of self-development for adolescents. The method of this service activity is to provide assistance and training to partners. The resulting results will be the ability of human resources in small businesses in optimizing skills in local youth organizations